Controlling as an Internal Process of Coordination of the Enterprise (Economic journal of Lesya Ukrainka Volyn National University, 2018)
In this article the authors were analyzed the concept of controlling, its component, the reasons for its occurrence at the moment and the importance of its functioning on the enterprise. The authors examined this tendency in considering the development of new trends in the economy. Also, the importance of using controlling as one of the important areas of effective operation of the enterprise was determined. The analysis of the preconditions for the emergence and development of controlling and the current state of the system in Ukraine was an important point in this article. The authors conclude that controlling allows you to analyze and respond to changes in environments at a fast pace.
Keywords: controlling, planning, coordination, management on enterprise, information